Pelaksanaan model pembelajaran TGT (Teams Games Tournaments) menggunakan quizizz pada peserta didik kelas X D mata pelajaran sosiologi di SMA Muhammadiyah 1 Pontianak - Hariani, Wiwin; Ramadhan, Iwan; Imanulyaqin, Muhammad Nur (Daya Nasional: Jurnal Pendidikan Ilmu-Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the implementation of the Team Games Tournament (TGT) learning model combined with the Quizizz application for Grade X D students in the Sociology subject at SMA Muhammadiyah 1 Pontianak. The research employed a qualitative approach with a descriptive design. Data were collected through observations, interviews, and evaluation tests to obtain a comprehensive overview of the learning process and outcomes. The results indicate that the application of the TGT model supported by Quizizz increased students"™ active participation, strengthened cooperation and communication among group members, and enhanced students"™ understanding of Sociology material. The use of Quizizz as an evaluation tool also provided immediate feedback, facilitated students"™ retention of concepts, and motivated healthy competition within groups. Furthermore, students"™ learning outcomes showed significant improvement after the implementation of this learning model. Based on these findings, it can be concluded that the TGT learning model supported by Quizizz is effective in improving students"™ motivation, engagement, and academic achievement in Sociology. This study recommends applying this learning model to other subjects at SMA Muhammadiyah 1 Pontianak to enhance the overall quality of learning